Banking for the Common Good: a case study. (11th December 2014) - Caldarelli, Adele; Fiondella, Clelia; Maffei, Marco; Spanò, Rosanna; Zagaria, Claudia
This research investigates how Italian mutual credit cooperative banks, understood as ethical banks, conceive and implement the intention to contribute to the Common Good. The literature highlights that it is a complex task to identify what, in practical terms, the Common Good consists of for an entity. Hence, we refer to a Common Good-driven theory, namely, Economia Aziendale, that has the potential to overcome the above-cited lack of practical application, thus strengthening the Common Good theory's ability to provide an appreciable framework for CSR and ethics studies. Economia Aziendale is used as a lens to analyse the case of the Banca di Credito Cooperativo di Napoli. The study provides a detailed picture of the values, activities and practices of the bank contributing to the achievement of the Common Good for the local community of Naples. The findings are of relevance for the international debate on ethics in finance.